2012
DOI: 10.5915/44-1-8780
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Medicine and Evolutionary Medicine: A Comparative Analysis

Abstract: The advent of evolutionary medicine in the last two decades has provided new insights into the causes of human disease and possible preventative strategies. One of the strengths of evolutionary medicine is that it follows a multi-disciplinary approach. Such an approach is vital to future biomedicine as it enables for the infiltration of new ideas. Although evolutionary medicine uses Darwinian evolution as a heuristic for understanding human beings’ susceptibility to disease, this is not necessarily in conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The high use of black seeds could be explained by religious factors and the use of prophetic medicine (Al-Tibb-e-Nabawi) (Ahmad et al, 2013, Elolemy and Albedah, 2012). This type of nonconventional medicine is derived from the holy Qura'an and the prophet Mohammed guide (Hadith) to treat or diagnose different diseases (Ahmad et al, 2013, AlRawi et al, 2017, Saniotis, 2012). Furthermore, this study showed that despite its potential drug-herb interactions, garlic ( Allium sativum) was used as a supplement by 21.5% of Saudi patients, and this prevalence was higher than the 11.7% reported among patients at Mayo Clinic in Minnesota (Prasad et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The high use of black seeds could be explained by religious factors and the use of prophetic medicine (Al-Tibb-e-Nabawi) (Ahmad et al, 2013, Elolemy and Albedah, 2012). This type of nonconventional medicine is derived from the holy Qura'an and the prophet Mohammed guide (Hadith) to treat or diagnose different diseases (Ahmad et al, 2013, AlRawi et al, 2017, Saniotis, 2012). Furthermore, this study showed that despite its potential drug-herb interactions, garlic ( Allium sativum) was used as a supplement by 21.5% of Saudi patients, and this prevalence was higher than the 11.7% reported among patients at Mayo Clinic in Minnesota (Prasad et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…1). This principle is adapted from Islamic references [12], but many of them are shared with other religions. In practice, halalopathy is proceeded through a combination of two approaches: mind-trust-drug and mind-trust-belief; in the first approach, the disease can be cured by trusted and rationally designed drugs whereas in the second approach trust is developed if the belief is rationally realized.…”
Section: Halalopathy: a Therapeutic Modelmentioning
confidence: 99%
“…The principles of halalopathy are mainly derived from Islamic references [12], and guidelines for the production of permissible therapy "halal pharma" have been implemented in many Muslim countries, thus the concept is mainly attractive for Muslim but still adaptable by other beliefs and lifestyles. To the best of our knowledge, halalopathy is the first to address entropy as the main target for prevention and cure.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the therapist has a determinant role to prepare a proper spiritual condition for the patient. A therapist who does not have a good spiritual state could not be successful during the treatment process [14,[35][36][37][38][39][40][41]. Also, as we mentioned, the high dignity of the spirit, according to Islamic doctrine, is attributed to the sincere faith in God.…”
Section: The Therapist and Spiritualitymentioning
confidence: 99%